Fitness consequences of divorce in the azure-winged magpie depends on the breeding experience of a new mate. Issue 1 (20th March 2020) - Gao, Li-Fang; Zhang, Hai-Yang; Zhang, Wen; Zhang, Xiao-Dan; Zhu, Zhen-Qin; Du, Bo
Abstract: Sexual conflict in producing and raising offspring is a critical issue in evolutionary ecology research. Individual experience affects their breeding performance, as measured by such traits of provisioning of offspring and engagement in extra-pair copulations, and may cause an imbalance in sexual conflict. Thus, divorce is hypothesized to occur within aged social pairs, irrespective of current reproductive success. This concept was explored in the azure-winged magpie Cyanopica cyanus by investigating the divorce of a social pair and its relationship to their changes in breeding performance with prior experience. Females engaging in extra-pair copulation may intensify sexual conflicts and may be the main reason for divorce. Once divorced, females repairing with an inexperienced male realized higher reproductive success than that repairing with an experienced male; males repairing with an experienced female realized higher reproductive success than that repairing with an inexperienced female. This finding indicates that the fitness consequence of divorce depends on the breeding experience of new mates. Divorced females can obtain more extra-pair copulations, whereas divorced males cannot, when they repair with inexperienced breeders. Divorced females provisioned a brood at lower rates than inexperienced females whereas divorced males had no such difference. It appears that divorced females can obtain an advantage in sexual conflicts with inexperienced mates in future reproduction. Consequently, females are probably more active than males in divorcing their aged mates so as to select an inexperienced male as a new mate. Azure-winged magpies thus provide novel insights into the implications of sexual conflict in birds.